Capital adjustment, technology vintages and training : role of capital investment spikes in firm’s skill formation strategy - Pardesi, Mantej [Verfasser]; Cörvers, Frank [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2025)
„We study how investment spikes in technologies and complementary infrastructure influence firms’ hiring and training strategies. While prior work emphasizes how technologies reallocate skill demand, few focus on how firms acquire the required skills. Using linked employer-employee data on German establishments, we identify spikes by their technological composition and capital vintages. Event study estimates show that investment spikes in ICT and production line technologies lead to an upscaling effect raising employment by external hiring followed by training of young apprentices. Combining technologies with factories and plants induces firms to use apprenticeship training without an increase in external hiring. Incumbent workers are trained when investment spikes renew the vintage of firm’s capital. Our findings support a vintage human capital framework in which technology adoption induces firms to gradually adjust workforce through hiring and training while preserving expertise of incumbent workers.” (authors’ abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; 370; 330; Unternehmen; Investitionen; Einflussfaktor; Ausbildungsverhalten; Personalgewinnung